The discharge process for a child with complex healthcare needs dependent on respiratory technology: A scoping review protocol - Cora O’Leary; Rachel Flynn; Serena FitzGerald; Helen Mulcahy; Margaret Curtin (PLoS ONE, 2026)
Background Children with complex healthcare needs spend a long time in hospital with frequent delays in discharge. This may be due to fluctuating health status, or contextual factors such as training carers, social circumstances, suitable housing, and community resources such as homecare nurses. Understanding the process for an effective discharge for children with complex healthcare needs who are respiratory technology dependent is essential to guide clinical practice, and shape policy that supports timely, coordinated, and family-centered transitions from hospital to home and inform evidenced-based research. Objective The aim of this scoping review is to gain an understanding of the discharge process for children with complex healthcare needs who are dependent on respiratory technology. Methods CINAHL, Medline, PsycINFO and Embase databases will be used for the literature search. Articles will be considered from peer reviews sources and English language text from 2015 owing to the increase in children with complex healthcare needs requiring respiratory technology and advances in complex care. Title and abstracts followed by full-text articles will be reviewed to determine which papers meet the inclusion criteria. Two reviewers will review each stage with further discussion as required for exclusion and inclusion. Data extracted will include information on key findings related to the aim and objectives of the scoping review and will be summarized and presented in tables and charts with a narrative summary. Expected Results International guidelines on care closer to home and caring for children with tracheostomies state the need for discharge pathways. This review will synthesis existing literature regarding the discharge processes of children with complex healthcare needs dependent on respiratory technology. Evidence will be organised across micro-level (child and family), meso-level (healthcare team and institutional processes), and macro-level (policy and system) influences. This scoping review will identify the multifaceted barriers and facilitator that impact the transition from hospital to home for children dependent on respiratory technology. Conclusion This review will identify current evidence from relevant studies in relation to discharge processes and provide detail on components and context.